Thermoplastic Polyurethanes-Fumed Silica Composites: Influence of NCO/OH in the Study of Thermal and Rheological Properties and Morphological Characteristics - Vega-Baudrit, José; Carballo, Sergio Madrigal; Martínez, José Miguel Martín (IntechOpen, 2012)
None